PENGARUH BUDAYA ORGANISASI SEKOLAH DAN SUPERVISI PEMBELAJARAN KEPALA SEKOLAH TERHADAP KINERJA GURU DI MADRASAH TSANAWIYAH (MTs) DI DISTRIK ABEPURA KOTA JAYAPURA - Diki Kurniawan (Universitas Cenderawasih, 2020)
The purpose of this study was to determine the influence of school organizational culture and the principal's learning supervision of teacher performance. Data was collected through a closed questionnaire to educators at madrasah - madrasah tsanawiyah at the junior high school level in Abepura District with a total of 3 schools. The number of samples is 38 people. Data analysis uses the help of a data processing application, namely SPSS 16. The results of the research include 1. the influence of school organizational culture on teacher performance with an r value of 0.379. This can be interpreted as a weak relationship. 2. There is an influence between learning supervision on teacher performance with an r value of 0.487. It can be interpreted that there is sufficient ridge 3. There is a significant influence between the culture of the school organization and the supervision of learning on teacher performance with a value of 0.523. Meanwhile, the contribution made by the X1 variable, namely the school organizational culture and the X2 variable, namely the supervision of the school principal's learning towards Y, namely the teacher's performance of 23.2%. The rest is obtained by other factors. Keywords: Organizational Culture, Learning Supervision, Teacher Performance